Adaptasi Kuliner Global: Ramen Halal sebagai Representasi Identitas dan Komodifikasi Budaya Muslim - Hasan, M Iqbal Amarul (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2025)
Globalization has accelerated the exchange of cultures, including in the culinary field. One interesting example of culinary adaptation in the era of globalization is halal ramen, which is an adaptation of traditional Japanese ramen to meet halal food standards for the Muslim community. This study aims to analyze halal ramen as a representation of Muslim identity amidst globalization and as an object of cultural commodification. Using a qualitative approach based on literature studies, this research examines three main aspects: (1) how halal ramen reflects Muslim identity; (2) how the commodification process can affect the cultural values of Japanese ramen; and (3) the ethical challenges in ensuring the halal status of food production. The findings show that halal ramen is not only a culinary adaptation that allows access for Muslim consumers but also reflects broader cultural interaction dynamics. Furthermore, the commodification of halal ramen in the global market reveals the potential for cultural homogenization that sacrifices traditional values. This study contributes to understanding the role of halal cuisine in fostering intercultural dialogue and offers recommendations for producers, regulators, and consumers in creating culinary innovations that respect religious and cultural values. This research provides a significant contribution to the literature on culinary globalization and halal food, serving as a reference for producers and regulators in presenting innovations that maintain cultural and religious values. Keywords: Halal ramen; Globalization; Muslim identity; Commodification; Culinary adaptation.